Selected Determinants of the Quality of Life of Patients with Degenerative Changes of the Spine - Sylwia Krzemińska; Agnieszka Nowak; Adriana Borodzicz; Ewelina Bąk; Anna Kostka (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Degenerative spinal disease is considered one of the most prevalent chronic diseases in Poland and worldwide. Sedentary lifestyle, lack of physical activity, and spinal overload contribute to this state of affairs. The chronic nature of the disease, along with pain and functional limitations of the musculoskeletal system, impact the quality of life.